The Effectiveness of Blended Learning Model on Students’ Psychomotor Skills in Pencak Silat - Sudirman, Ridwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The background of this research is the new normal activity after the Covid-19 pandemic which possible the application of blended learning, so the pencak silat learning materials experience a transition from face-to-face learning to online learning. This study aims to determine how much the effectiveness of blended learning implementation to students’ Pencak Silat psychomotor skills. The research method is used the experimental method of one group pretest-postest design. The population of this study is 420 students, with a sampling technique uses pisposive sampling for 76 students. The instrument is used a test with parametric statistical data analysis techniques t test. The results showed that, there is a significant influence (t count 7.79 > t table 2.415) on Pencak Silat course after the blended learning is applied. The influence is resulted; it is classified as a high percentage of increase %. Based on the results of this study, blended learning method gives a significant influence on the psychomotor skills of Pencak Silat in students compared to online learning method.